2009
DOI: 10.1590/s0102-311x2009000500006
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de medidas de controle da esquistossomose mansoni no Município de Sabará, Minas Gerais, Brasil, 1980-2007

Abstract: Schistosomiasis control programs in Brazil have helped reduce prevalence and the severe forms of the disease, but have failed to prevent new foci from appearing, especially on the periphery of large cities. The current article aims to assess the prevalence of schistosomiasis and the presence of intermediates hosts for Schistosoma mansoni in the district of Ravena, Municipality of Sabará, Minas Gerais State, Brazil, 27 years after implementing water treatment and specific treatment for infected individuals. Rav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
(22 reference statements)
1
3
0
7
Order By: Relevance
“…The occurrence of a higher number of cases of the disease in young adults may be related to their work, given that this age group is more productive and, consequently more exposed, which can be corroborated by other studies 23,24 . On the other hand, schoolchildren (regardless of gender) were observed to be more exposed to activities related to using river water for leisure.…”
Section: Discussionsupporting
confidence: 76%
“…The occurrence of a higher number of cases of the disease in young adults may be related to their work, given that this age group is more productive and, consequently more exposed, which can be corroborated by other studies 23,24 . On the other hand, schoolchildren (regardless of gender) were observed to be more exposed to activities related to using river water for leisure.…”
Section: Discussionsupporting
confidence: 76%
“…Various early studies demonstrated that improvement of the sanitary conditions and treatment of positive patients contribute to reduce morbidity and prevalence of the disease [4] – [11] . A study carried out in Comercinho/MG, Brazil, in 1974, clearly shows these facts.…”
Section: Introductionmentioning
confidence: 99%
“…Conforme foi observado em São João Evangelista, outros estudos em Minas Gerais indicaram aumento de áreas com baixa prevalência de esquistossomose nos últimos anos, em detrimento de regiões com alta endemicidade 18 . Um levantamento epidemiológico realizado em 390 municípios da área endêmica desse Estado, no período O percentual de positividade para esquistossomose também sofreu considerável queda ao longo da série sob estudo, excetuando-se o viés amostral de 2008, em que somente 104 exames foram realizados e a positividade foi de 19,2%.…”
Section: Materiais E Métodosunclassified
“…Entretanto, é válido salientar que a menor ocorrência das parasitoses pode ser atribuída à interferência de outros fatores socioeconômicos que se elevaram, como, por exemplo, o grau de escolaridade e o acesso aos serviços de saúde. Um estudo realizado por Vasconcelos et al 18 , de 1980 a 2007, em Ravena, distrito de Sabará, estado de Minas Gerais, apontava uma prevalência geral de esquistossomose de 36,7% e de 11,6% no grupo de crianças e adolescentes na faixa etária de 0 a 14 anos em 1980; a qual decaiu, respectivamente, para 2,5% e 0,7% nos mesmos grupos em 2007. Foi observada uma mudança de hábitos das pessoas quanto à utilização das águas das coleções hídricas para tarefas domésticas, com a introdução de água potável em mais de 95,0% das residências do Distrito 18 .…”
Section: Materiais E Métodosunclassified